Phosphorylation of hydroxylysine residues in collagen synthesized by cultured aortic smooth muscle cells. - Urushizaki, Y (Proc Natl Acad Sci U S A, 1985)
O5-Phosphohydroxylysine was chemically synthesized and techniques were established for its identification by combined use of cation-exchange chromatography, thin-layer electrophoresis at pH 1.9 and 3.5, and thin-layer chromatography. Clean separation of phosphohydroxylysine from the other phospho amino acids, phosphoethanolamine, and phosphocholine was achieved. Conditions were also determined to permit hydrolysis of proteins in 2 M HCl without loss of the phosphono group of phosphohydroxylysine residues. Experiments were then performed showing that 32P was incorporated into the hydroxylysine residues of cell-associated collagens when cultured calf aorta medial smooth muscle cells were incubated with [32P]orthophosphate. In other experiments, the cells incorporated [3H]lysine into hydroxylysine residues of cell-associated collagen and then 32P into phosphohydroxylysine residues. The doubly labeled phosphohydroxylysine subsequently isolated showed nearly 1:1 stoichiometry with respect to incorporation of precursor lysine and phosphorus. Finally, in preliminary experiments done with a cell-free extract of the smooth muscle cells, 32P was transferred from [gamma-32P]ATP to hydroxylysine residues in several kinds of collagenous substrates. Thus, this work shows that smooth muscle cells have the capacity to phosphorylate hydroxylysine residues in their cell-associated collagens and provides preliminary evidence that a protein kinase is involved. IMAGES: